More Diversity, Same Framework: A Comparative Analysis of Video Platforms and Aggregated Platforms in China - Ke Jiang (International Journal of Computational and Experimental Science and Engineering, 2025)
With the in-depth development of social networks and the Internet revolution, the diversity of news in the digital age is worthy of attention. Video websites have more independent players, allowing them to publish more alternative news than mainstream media. How much the penetration rate of different institutions affects platform diversity, and whether and to what extent video news sites can break through the mainstream news reporting framework are some concerns. This study selects digital platforms with different penetration rates of Chinese organizations. Taking Tokyo Olympics reports as a sample, an evaluation system for news diversity was built, and Simpson's diversity index was measured from the perspective of content diversity, including national visibility, medal coverage ratio, and athlete visibility. Through PCA dimensionality reduction analysis, news keywords of different platforms are extracted, and news reporting frameworks of different platforms are visualized. Results show that video websites have a lower penetration rate and more diversity and coverage of different actors. However, it is still possible for video platforms and aggregation sites to be under the convergent news framework. Abandoning a certain degree of news diversity and maintaining the convergent news framework may serve as a strategy to assist China's digital age news propaganda.